Transport, functions, and interaction of calcium and manganese in plant organellar compartments. Issue 4 (12th March 2021) - He, Jie; Rössner, Nico; Hoang, Minh T T; Alejandro, Santiago; Peiter, Edgar
Abstract: Calcium (Ca 2+ ) and manganese (Mn 2+ ) are essential elements for plants and have similar ionic radii and binding coordination. They are assigned specific functions within organelles, but share many transport mechanisms to cross organellar membranes. Despite their points of interaction, those elements are usually investigated and reviewed separately. This review takes them out of this isolation. It highlights our current mechanistic understanding and points to open questions of their functions, their transport, and their interplay in the endoplasmic reticulum (ER), vesicular compartments (Golgi apparatus, trans -Golgi network, pre-vacuolar compartment), vacuoles, chloroplasts, mitochondria, and peroxisomes. Complex processes demanding these cations, such as Mn 2+ -dependent glycosylation or systemic Ca 2+ signaling, are covered in some detail if they have not been reviewed recently or if recent findings add to current models. The function of Ca 2+ as signaling agent released from organelles into the cytosol and within the organelles themselves is a recurrent theme of this review, again keeping the interference by Mn 2+ in mind. The involvement of organellar channels [e.g. glutamate receptor-likes (GLR), cyclic nucleotide-gated channels (CNGC), mitochondrial conductivity units (MCU), and two-pore channel1 (TPC1)], transporters (e.g. natural resistance-associated macrophage proteins (NRAMP), Ca 2+ exchangers (CAX), metal tolerance proteins (MTP), and bivalent cation transporters (BICAT)], and pumps [autoinhibited Ca 2+ -ATPases (ACA) and ER Ca 2+ -ATPases (ECA)] in the import and export of organellar Ca 2+ and Mn 2+ is scrutinized, whereby current controversial issues are pointed out. Mechanisms in animals and yeast are taken into account where they may provide a blueprint for processes in plants, in particular, with respect to tunable molecular mechanisms of Ca 2+ versus Mn 2+ selectivity. Abstract : Calcium and manganese play essential roles in organellar compartments, yet they share many transport mechanisms, implying synergistic, and antagonistic interactions of both cations.